DESIGN OF SMARTSCHOOL WEBCAM SECURITY SYSTEM USING RASPBERRY PI WITH MOTION DETECTION IN SMK PGRI SUKODADI - Firman Yudianto; Fajar Annas Susanto (JOURNAL ASRO, 2020)
Currently a low cost security system is needed and easy to apply especially at educational institutions that willimplement smart school and industry 4.0. Needed devices are raspberry pi and web camera. Raspberry pi willonly save moving images taken from the web camera. Because by storing an image whose file size is not toolarge will ease the performance of the server. In this study, a design for the raspberry pi based motion detectionsystem will be applied at SMK PGRI Sukodadi Lamongan Regency which has not have security system. Thissystem will save the file in the form of an image that will be put together into a moving image that looks like avideo that will displayed in a LED monitor.Keywords: smart school, motion detection, moving image.